MAKNA KATA KUBI (LEHER) YANG MENGANDUNG MAKNA KIASAN (METAFORA DAN METONIMI) - Setiyansa, Riani; Hermandra, Hermandra; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstarct: In this study described the meaning of the word kuubi (neck) which contains the meaning of figurative (metaphors and metonymys). Figurative meaning is a word or group of word that is not the true meaning, but to makes something up. In the figurative meaning there are various types of majas, one of them are metaphors and metonymys. Metaphor is a change of meaning of the equality of properties between two objects, while metonymy is a figuration which uses the feature or label and object to replace particular object. This research is a qualitative research with intralingual method. The theory used in this research is the theory of metaphor by Lakoff (1980) and Keraf (2006) and the theory of metonymy by Ullman (1997). The result of this research is found the meaning of word kubi (neck) which contains figurative mean as much as 12 data. 6 data including metaphor and 6 data including metonymy. The results of this study indicated that Japanese choose to use the word kubi (neck) in a sentences that contains figurative meaning which its mean related with the function of neck and associated with life and work.Keywords : Figurative Meanings, Kubi (Neck), Metaphor, Metonyms